The utilization of composite material: Water hyacinth and sugarcane bagasse fiber-epoxy for cool box thermal insulation - Ivinia Muthia Anjani; Raden Grenny Sudarmawan; Noor Hidayati; Muslimin Muslimin (University of Muhammadiyah Malang, 2023)
Fish serves as the primary income source for the majority of fishermen in Indonesia. In order to preserve the freshness of the fish, fishermen commonly use styrofoam cool boxes. However, the use of styrofoam results in a significant quantity of waste that doesn't naturally break down. As a solution, a study was conducted to develop an alternative thermal insulation material for cool boxes. This material takes the form of a biocomposite, made from epoxy resin combined with water hyacinth and sugarcane bagasse fibers. The research’s results are A1 type had the lowest density value (0,795 g/cm3) and the lowest thermal conductivity value (0,1987 W/mK). The B3 type had the highest bending strength value (395,224 kg/cm2). All type of ratio variations’ density and bending strength test results are met the requirements of SNI 03-2105-2006. It can be concluded that A1 type is the best choice as a thermal insulation material purpose. After a cool box from composite (A1) manufactured, a comparison test between styrofoam cool box and composite cool box is being held. The 24-hour test result shows that styrofoam cool box still outperformed the composite cool box in terms of temperature maintenance.